1905 Pa. Laws 279-80, No. 189, § 1. - (:unkn) unknown (General Publisher, 1905)
Be it enacted, that if any person shall willfully and maliciously, either by day or by night, with or without breaking, enter any building with intent to commit a felony by the use of nitroglycerine, dynamite, gunpowder, or other high explosives, such person shall be guilty of felony, and, upon conviction, shall be sentenced to pay a fine not exceeding one thousand dollars, and undergo an imprisonment, by separate and solitary confinement at labor, not exceeding twenty-five years.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME